2021
DOI: 10.1088/1361-6587/ac2e40
|View full text |Cite
|
Sign up to set email alerts
|

Two-fluid approach to weak plasma turbulence

Abstract: Weakly turbulent processes that take place in plasmas are customarily formulated in terms of kinetic theory. However, owing to an inherent complexity associated with the problem, thus far the theory is fully developed largely for unmagnetized plasmas. In the present paper it is shown that a warm two fluid theory can successfully be employed in order to partially formulate the weak turbulence theory in spatially uniform plasma. Specifically, it is shown that the nonlinear wave-wave interaction, or decay process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…demonstrated that the warm two-fluid theory is capable of partially reproducing the weak turbulence wave equation for unmagnetized plasmas, which is normally derived from full kinetic theory. 81 The present paper adopted such an approach, which is combined with quasilinear kinetic theory, and succeeded in formulating the weak turbulence theory for magnetized plasmas under the assumption of electrostatic interaction.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…demonstrated that the warm two-fluid theory is capable of partially reproducing the weak turbulence wave equation for unmagnetized plasmas, which is normally derived from full kinetic theory. 81 The present paper adopted such an approach, which is combined with quasilinear kinetic theory, and succeeded in formulating the weak turbulence theory for magnetized plasmas under the assumption of electrostatic interaction.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…[49][50][51] A method was recently proposed to overcome such a difficulty. In a recent work, 81 one of the present authors (P.H.Y.) noted that one can partially reformulate the kinetic weak turbulence theory by resorting to the warm two-fluid theory.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation